Learning Operations Research online: benefits, challenges, and experiences. (26th May 2009) - Faulin, Javier; Juan, Angel A.; Fonseca, Pau; Pla, Lluis M.; , Sara V. Rodriguez
Information technologies offer new ways to teach and learn Operations Research (OR): on the one hand, they have driven the growth of distance learning opportunities; on the other hand, they facilitate the shifting to an emergent educational paradigm, which considers students as active and central actors in their learning process. The use of computer software and collaborative e-learning as methodological policies to increase students' motivation for OR are also discussed in this paper. Thus, we describe lessons learned in some real experiences, developed during the last years at four different universities in Spain, regarding the teaching and learning of OR.